2013
DOI: 10.1177/1470320313501217
|View full text |Cite
|
Sign up to set email alerts
|

The insertion-deletion polymorphism of the ACE gene is associated with increased blood pressure in women at the end of pregnancy

Abstract: Introduction: Malfunctioning of the cardiovascular system during pregnancy may be responsible for adverse effects on the 'mother-fetus' system. The cardiovascular system of a pregnant woman develops adaptation to the increased load. Angiotensin-converting enzyme (ACE) is known to play an important role in the adaptation. The present study was designed to investigate whether the insertion-deletion (I/D) polymorphism of the ACE gene is associated with the level of arterial blood pressure in women before and duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
0
29
0
6
Order By: Relevance
“…Finally, the response to vasodilation has primarily focused on genetic variation of the ACE-inhibitor, angiotensin, and the angiotensin-II receptor. Specifically, the deletion variant of ACE (rs7079), the C variant of Angiotensin (rs699), and the C variant of the angiotensin-II receptor (rs5186) have shown enhanced response to ACE-inhibition and angiotensin receptor antagonism [44][45][46]. Collectively, these data demonstrate genetic variation may be partially responsible for the variability in effectiveness to HTN therapy and, possibly, the bell-curve response noted previously.…”
Section: Resultsmentioning
confidence: 64%
“…Finally, the response to vasodilation has primarily focused on genetic variation of the ACE-inhibitor, angiotensin, and the angiotensin-II receptor. Specifically, the deletion variant of ACE (rs7079), the C variant of Angiotensin (rs699), and the C variant of the angiotensin-II receptor (rs5186) have shown enhanced response to ACE-inhibition and angiotensin receptor antagonism [44][45][46]. Collectively, these data demonstrate genetic variation may be partially responsible for the variability in effectiveness to HTN therapy and, possibly, the bell-curve response noted previously.…”
Section: Resultsmentioning
confidence: 64%
“…Another study in a group of obese children and adolescents found that the DD and ID genotypes were associated with a higher prevalence of hypertension in boys but not in girls, compared to the II genotype [ 123 ]. The D allele of the ACE gene was also associated with higher BP in pregnant women [ 124 ]. However, other studies have failed to confi rm a signifi cant relation between ACE I/D polymorphism and the risk of hypertension (Chaps.…”
Section: Heterogeneity Of the Ace Genementioning
confidence: 96%
“…There is a large number of works devoted to the study of genetic susceptibility to various pathologies. The search for the associations of polymorphic genetic loci with a disease is widely used currently (3,(7)(8)(9)(10)12).…”
Section: Introductionmentioning
confidence: 99%